De-policing and crime in the wake of Ferguson: Racialized changes in the quantity and quality of policing among Missouri police departments. (May 2017) - Shjarback, John A.; Pyrooz, David C.; Wolfe, Scott E.; Decker, Scott H.
Abstract: Purpose: This study explored whether police departments have engaged in "de-policing"—withdrawal from active police work—in response to unprecedented levels of negative attention, as well as the correlates of changes in police behavior. Methods: Using data from 118 of the 121 police departments serving jurisdictions over 5000 residents in Missouri, we examined changes in both the quantity (rates of vehicle/traffic stops, searches, and arrests) and quality ("hit rates" from searches) of policing from 2014 to 2015 and whether de-policing corresponded with year-over-year changes in crime rates. Results: The findings revealed a − 0.11 standardized change in stops (around 67, 000 fewer stops in 2015 than 2014) and a 0.17 standardized change in hit rates (nearly 2 percentage points). Multivariate models indicated that departments serving larger African-American populations conducted fewer stops ( β  = − 0.44), searches ( β  = − 0.37), and arrests ( β   =  − 0.27) in 2015 compared to 2014, although race was unrelated to changes in hit rates. Changes in police behavior had no appreciable effect on total, violent, or property crime rates. Conclusions: The negative attention and increased scrutiny of law enforcement appears to have had an impact on traffic stops and hit rates in Missouri. Given the racialized findings, training and community-outreach programs should aim to increase mutual trust among the police and African-American communities. Also, increasing organizational justice within departments might be one way to improve officer morale and increase motivation in the current policing climate. Highlights: We examined whether "de-policing" has occurred among a sample of Missouri police departments in the wake of Ferguson. Results indicate that agencies made fewer traffic stops but yielded higher contraband "hit rates" in 2015 compared to 2014. Departments were more likely to engage in de-policing in jurisdictions with higher percentages of African-American residents. Changes in traffic stops and hit rates have not corresponded with increases in total, violent, or property crime rates.